The tractor story - Innes Trevor (UK History, Stroud, 2011, 2014)
"Over 100 tractors, stretching back over 100 years--from the first steam engines on wheels produced by ingenious engineers in the garden shed, to the mighty multinational John Deere. They are all here, photographed across the globe, from Kent to Canberra."--Publisher's description